Prevalence and factors affecting tobacco use among urban adolescents in Bhilai city, central India - Nayak, Snehamayee; Mishra, Abhisek (International Journal Of Community Medicine And Public Health, 2018)
Background: Most tobacco users initiate their smoking habit quite young, upto 10 yrs of age. The physiological and psychological changes in this phase of life with an inquisitiveness to become autonomous enhance their vulnerability for addiction, tobacco use and dependency. its use during adolescence are likely to continue the use into adulthood and contribute to the 90 per cent of premature deaths among tobacco users. In this context the prevalence, patterns and correlates of tobacco use are studied among adolescent of urban slums of Bhilai city, Chhattisgarh India. Methods: Total 172 adolescents within the age group of 10-19 yrs, across 30 slums of Bhilai city are taken by cluster random sampling. They have been administered a self-administered questionnaire incorporating standardized instruments. Results: Of the 172 study respondents, the overall lifetime prevalence of tobacco use is 25 per cent (18% boys and 7% girls). Among users category the prevalence of tobacco use increased from 2.3 per cent at 10-14 yrs to 58.2 per cent at 18-19 yr. The mean age of onset of tobacco use was 14.8±3.1 yr. The prevalence is higher among subjects belong to lower socio-economic status and those with part-time jobs. Tobacco users had significantly higher rates of use of alcohol (90%) than tobacco non users (7.8%). They are having any form of stress in family (55% vs. 31.5%), more severe psychological distress (65 vs. 25.6%) and a sense of hopelessness (40 vs. 19%). Conclusions: The prevalence of tobacco use in adolescents reported in this study is relatively higher than those reported from other Indian States. However, it correlates with multiple socio-demographic and familial predicting factors suggesting a need to promote health and holistic interventions to prevent adolescent tobacco use.